Variation and process of life history evolution in insular dwarfism as revealed by a natural experiment - Hayashi, Shoji; Kubo, Mugino O.; Sánchez-Villagra, Marcelo R.; Taruno, Hiroyuki; Izawa, Masako; Shiroma, Tsunehiro; Nakano, Takayoshi; Fujita, Masaki (Frontiers in Earth Science, 2023)
Islands are a classic focus for evolutionary studies. One topic of great interest has been the evolution of “dwarfs,” significantly smaller island mammals relative to their continental counterparts. Although a consensus has been achieved regarding the multivariate ecological causes behind changes in body size, the processes involved remain largely unexplored. Life history variables, including age at first reproduction, growth rate, and longevity, are likely to be key to understanding the process of insular dwarfism. The Japanese archipelago, with its numerous islands, offers a unique natural experiment for the evolution of different sizes within the same group of organisms; namely, deer. Thus, we investigated eight deer populations with a total number of 52 individuals exhibiting body size variation, both extant and fossil, to clarify the effect of insularity on life history traits. We applied several methods to both extant and extinct populations to resolve life history changes among these deer populations. Skeletochronology, using lines of arrested growth formed in long bones (femur and tibia), successfully reconstructed body growth curves and revealed a gradual change in growth trajectories reflecting the degree of insularity. Slower growth rates with prolonged growth periods in more isolated deer populations were revealed. An extensive examination of bone microstructure further corroborated this finding, with much slower growth and later somatic maturity evident in fossil insular deer isolated for more than 1.5 Myr. Finally, mortality patterns assessed by demographic analysis revealed variation among deer populations, with a life history of insular populations shifting toward the “slow life.”